Recent speciation in the Indo-West Pacific: rapid evolution of gamete recognition and sperm morphology in cryptic species of sea urchin. - Landry, C (2003)
The rich species diversity of the marine Indo-West Pacific (IWP) has been explained largely on the basis of historical observation of large-scale diversity gradients. Careful study of divergence among closely related species can reveal important new information about the pace and mechanisms of their formation, and can illuminate the genesis of biogeographic patterns. Young species inhabiting the IWP include urchins of the genus Echinometra, which diverged over the past 1-5 Myr. Here, we report the most recent divergence of two cryptic species of Echinometra inhabiting this region. Mitochondrial cytochrome oxidase 1 (CO1) sequence data show that in Echinometra oblonga, species-level divergence in sperm morphology, gamete recognition proteins and gamete compatibility arose between central and western Pacific populations in the past 250 000 years. Divergence in sperm attachment proteins suggests rapid evolution of the fertilization system. Divergence of sperm morphology may be a common feature of free-spawning animals, and offers opportunities to simultaneously understand genetic divergence, changes in protein expression patterns and morphological evolution in traits directly related to reproductive isolation.